-6x-(9y+(5x-(-2y-b))-(2b+a))=

Simple and best practice solution for -6x-(9y+(5x-(-2y-b))-(2b+a))= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x-(9y+(5x-(-2y-b))-(2b+a))= equation:


Simplifying
-6x + -1(9y + (5x + -1(-2y + -1b)) + -1(2b + a)) = 0

Reorder the terms:
-6x + -1(9y + (5x + -1(-1b + -2y)) + -1(2b + a)) = 0
-6x + -1(9y + (5x + (-1b * -1 + -2y * -1)) + -1(2b + a)) = 0
-6x + -1(9y + (5x + (1b + 2y)) + -1(2b + a)) = 0

Reorder the terms:
-6x + -1(9y + (1b + 5x + 2y) + -1(2b + a)) = 0

Remove parenthesis around (1b + 5x + 2y)
-6x + -1(9y + 1b + 5x + 2y + -1(2b + a)) = 0

Reorder the terms:
-6x + -1(9y + 1b + 5x + 2y + -1(a + 2b)) = 0
-6x + -1(9y + 1b + 5x + 2y + (a * -1 + 2b * -1)) = 0
-6x + -1(9y + 1b + 5x + 2y + (-1a + -2b)) = 0

Reorder the terms:
-6x + -1(-1a + 1b + -2b + 5x + 9y + 2y) = 0

Combine like terms: 1b + -2b = -1b
-6x + -1(-1a + -1b + 5x + 9y + 2y) = 0

Combine like terms: 9y + 2y = 11y
-6x + -1(-1a + -1b + 5x + 11y) = 0
-6x + (-1a * -1 + -1b * -1 + 5x * -1 + 11y * -1) = 0
-6x + (1a + 1b + -5x + -11y) = 0

Reorder the terms:
1a + 1b + -6x + -5x + -11y = 0

Combine like terms: -6x + -5x = -11x
1a + 1b + -11x + -11y = 0

Solving
1a + 1b + -11x + -11y = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-1b' to each side of the equation.
1a + 1b + -11x + -1b + -11y = 0 + -1b

Reorder the terms:
1a + 1b + -1b + -11x + -11y = 0 + -1b

Combine like terms: 1b + -1b = 0
1a + 0 + -11x + -11y = 0 + -1b
1a + -11x + -11y = 0 + -1b
Remove the zero:
1a + -11x + -11y = -1b

Add '11x' to each side of the equation.
1a + -11x + 11x + -11y = -1b + 11x

Combine like terms: -11x + 11x = 0
1a + 0 + -11y = -1b + 11x
1a + -11y = -1b + 11x

Add '11y' to each side of the equation.
1a + -11y + 11y = -1b + 11x + 11y

Combine like terms: -11y + 11y = 0
1a + 0 = -1b + 11x + 11y
1a = -1b + 11x + 11y

Divide each side by '1'.
a = -1b + 11x + 11y

Simplifying
a = -1b + 11x + 11y

See similar equations:

| 2t^2-20t=0 | | 2(3v-1)+7v+7=5(v-6)+3v | | 304=s+20 | | 304=s+20w | | (4+w)(5w-8)=0 | | 30+9y=16y | | 5(w+2)-6(w+4)=0 | | (-6x-z)-(3y+(7x-(3z+8y+x)))= | | (5w+6)(5w-6)= | | -X+2x^2=0 | | -(8y+2)-(-7y-5)=-1 | | B=b+2a+3c | | 8(3x-8)=2(12x+7) | | (18y^2-12xy)-(6y^2+xy-a)= | | 3+3s-2=8s+5-3s | | 4(3w+1)+4v=4(v-6)-2v | | 6t+8t=84 | | 9ln(4x)=54 | | 6ay^3+5ay^2-4ay= | | (2.25c-9.28b+3.82a)-(-3.92a-1.72b-8.33c)= | | 2p=5p+9 | | 90=2x*3x+1+5*5 | | -8(3b+2)+(25b-9)=0 | | (23y^2+4y^3-12)-(11y^3-8y^2+y)= | | 3.1q-2.2-5.3q=-3.2q-1.2 | | 9+x^2=0 | | 39=x+5 | | 2.2q-4.7-4.5q=3.3q-3.7 | | 39=x+5*3 | | (2z+5c-3a)-(6a+2c-4z)= | | -3(x+4)+13=-2x-11 | | (y-z-b)-(b+y+z)= |

Equations solver categories